Emulsion templating of poly(lactic acid) particles droplet formation behavior - Vladisavljević, Goran T (Langmuir : the ACS journal of surfaces and colloids, 2012)
Monodisperse poly(DL-lactic acid) (PLA) particles of diameters between 11 and 121 μm were fabricated in flow focusing glass microcapillary devices by evaporation of dichloromethane (DCM) from emulsion droplets at room temperature. The dispersed phase was 5% (w/w) PLA in DCM containing 0.1-2 mM Nile Red and the continuous phase was 5% (w/w) poly(vinyl alcohol) in reverse osmosis water. Particle diameter was 2.7 times smaller than the diameter of the emulsion droplet template, indicating very low particle porosity. Monodisperse droplets have only been produced under dripping regime using a wide range of dispersed phase flow rates (0.002-7.2 cm(3)·h(-1)), continuous phase flow rates (0.3-30 cm(3)·h(-1)), and orifice diameters (50-237 μm). In the dripping regime, the ratio of droplet diameter to orifice diameter was inversely proportional to the 0.39 power of the ratio of the continuous phase flow rate to dispersed phase flow rate. Highly uniform droplets with a coefficient of variation (CV) below 2% and a ratio of the droplet diameter to orifice diameter of 0.5-1 were obtained at flow rate ratios of 4-25. Under jetting regime, polydisperse droplets (CV > 6%) were formed by detachment from relatively long jets (between 4 and 10 times longer than droplet diameter) and a ratio of the droplet size to orifice size of 2-5